Sosialisasi Membangun Sumber Daya Manusia Mahasiswa FKIP Undana Berbasis Bela Negara - Silitonga, Tatar Bonar; Adriyanto, Agus; Taneo, Melkisedek; Messakh, Jakobis; Manesi, Damianus (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
This dedication aims to socialize and develop the human resources of FKIP Undana students based on the concept of national defense. FKIP Undana students have an important role in nation-building and need a deep understanding of the spirit of national defense and relevant skills. The community service activities are carried out in three stages: preparation, implementation, and evaluation. This dedication is a collaboration between the Defense University of the Republic of Indonesia and Nusa Cendana University. Socialization and discussion methods are employed in implementing the community service to FKIP Undana's community. The Participatory Action Research (PAR) approach is used to enhance the capacity and capabilities of students in the spirit of national defense. This approach aims to develop collective critical awareness of students' roles in a diverse society and the global challenges to national sovereignty. The results of this dedication indicate that the management of students' human resources (HR) in the context of national defense plays a crucial role in building capacity, increasing awareness, developing leadership, collaboration, and utilizing technology and social media. With effective HR management, students can become a strong force in the spirit of national defense, actively participate in national defense activities, prepare themselves as future generations ready to face national security challenges, and build cross-border relationships. Furthermore, the efforts of students as intellectual cadres include the development of critical thinking, innovation, information dissemination, constructive criticism, and supervision. The implementation of national defense among students can be carried out by incorporating national defense materials into the academic curriculum, organizing seminars and discussions, conducting physical and mental exercises, encouraging participation in national defense activities beyond the campus, and fostering awareness and the spirit of national defense through campus life.